2010
DOI: 10.1149/1.3290733
|View full text |Cite
|
Sign up to set email alerts
|

Low Resistance High Reflectance ITO/Al Ohmic Contacts to p-Type GaN Via SF[sub 6] Plasma Treatments

Abstract: We demonstrate improved electrical and optical properties of indium tin oxide ͑ITO͒/Al reflectors, via SF 6 plasma treatments, for vertical-type GaN light emitting diodes. A 200 nm thick ITO film was deposited and annealed at 650°C to obtain ohmic contacts with p-GaN, after which SF 6 and O 2 plasma were applied on ITO before the Al deposition to effectively increase the work function of ITO and decrease the roughness of the ITO surface. The SF 6 plasma-treated ITO/Al reflector showed the lowest specific conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…GaN-based light emitting diodes (LEDs) are promising solid state lighting devices as an alternative to the fluorescent light lamp. Vertical-structure LEDs by laser lift-off (LLO) were exploited in GaN-based LEDs to improve the light extraction efficiency and thermal management of the devices . In these configurations, Ohmic contacts with low contact resistance and high reflectance are essential in improving the electrical and optical performance of the devices.…”
Section: Introductionmentioning
confidence: 99%
“…GaN-based light emitting diodes (LEDs) are promising solid state lighting devices as an alternative to the fluorescent light lamp. Vertical-structure LEDs by laser lift-off (LLO) were exploited in GaN-based LEDs to improve the light extraction efficiency and thermal management of the devices . In these configurations, Ohmic contacts with low contact resistance and high reflectance are essential in improving the electrical and optical performance of the devices.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Al‐based reflectors have increasingly attracted interest as an alternative, because they have high reflectance in the visible and UV spectra. However, there is a critical problem with Al‐based reflectors; Al has a low work function, and therefore, Al can form ohmic contacts only to n‐type GaN, but not to p‐type GaN . To solve this problem, nanopixel contacts (size: 1 × 1 µm 2 ) were combined with Al reflectors to enhance the light extraction in UV LEDs .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Lee et al, demonstrated ITO/Al contacts to p-GaN epitaxial film with SF 6 plasma treatments on sapphire. 27 D. Selvanathan et al reported SiCl 4 plasma treatment for formation of low-resistance metal based ohmic contacts on AlGaN/GaN heterostructure field effect transistors. 28 On the other hand, Li et al, reported the role of N 2 and BCl 3 /Cl 2 plasma treatments on GaN surfaces for the formation of metal-based ohmic contact to n-GaN thin film on sapphire.…”
mentioning
confidence: 99%